TRANSFORMATIONAL LEADERSHIP, JOB COMPETENCE, AND JOB SATISFACTION AS A CRITICAL PREDICTOR OF EMPLOYEE PERFORMANCE: A QUANTITATIVE STUDY - Indrio, Ludita Woro; Herachwati, Nuri (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
Every employee has the same goal: to be successful and develop where they currently work. For a business to be successful, it needs to promote the performance of its employees. This study uses quantitative methods to explore the influence of transformational leadership and job competence on job satisfaction and their impact on employee performance. The research was conducted at PT BPRS Bhakti Sumekar Sumenep, with a total sample of 91 employees participating. After testing the hypothesis using the Multivariate Analysis Structural Equation Model Partial Least Square (SEM-PLS), the research findings reveal that transformational leadership and job competence have a positive and significant effect on job satisfaction and impact employee performance. Theoretical and practical implications are examined in this study.